Innovations in ICT Use in Library and Information Science Education through Distance Mode: An Experience - Gupta, Dinesh K (Journal of Information and Knowledge, 2017)
Library and Information Science Programmes in India - from certificate programme to the research degree programs at doctoral level are being offered by more than one hundred universities/ institutions. Vardhman Mahaveer Open University offers a variety of Library and Information Science Programmes including a Certificate Programme in Digital Libraries (CPDL) and is a leader in the programmes offered in Hindi language. The University has employed various technologies to support learners starting from online admission to making available courses material online. This paper highlights the key features of the CPDL.